PENYERAPAN AIR DAN KELARUTAN RESIN KOMPOSIT TIPE MICROHYBRID, NANOHYBRID, PACKABLE DALAM CAIRAN ASAM - Arlina Nurhapsari; Andina Rizkia Putri Kusuma (ODONTO : Dental Journal, 2018)
Background: Composite resin is the most widely used restoration material. This material is composed of several materials such as polymer matrix, fller particles and silane coupling agents. As technology progresses, microhybrid, nanohybrid and packable composite resin materials are developed, with good handling and mechanical properties. As a polymer-based material, the composite resin absorbs the liquid, causing the solubility of the resin matrix. Carbonated drinks and chlorine, are acidic liquids that can cause soluble resin matrix. The aim of this paper is to compare water sorption and solubility between composite resin type microhybrid, nanohybrid, packable from diﬀerent brand.Methods: This research used experimental method with sample of composite resin disk with diameter 15 mm and thickness 1 mm. The number of samples was 90 divided into 18 treatment groups, 9 group immersed in carbonated drinks and 9 group immersed in chlorine. The grouping is based on composite resin type microhybrid, nanohybrid, packable from diﬀerent brand. Water sorption is measured by the sample mass diﬀerence before and after immersion then divided by the initial volume of the sample. While the solubility of the composite resin was measured by reducing the sample mass prior to submersion and afterdrying then divided by the initial volume of the sample.Result: The results showed signifcant diﬀerences in water sorption on chlorine, solubility in carbonated beverages and chlorine. Meanwhile, an insignifcant diﬀerence occurred in water sorption in carbonated beverages.Conclusion: water sorption and solubility in 3 types of composite resin with9 diﬀerent product, not depend on the composite resin type but depend on the product used